Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a.
\(A=5.\left(2^2\right)^{15}.\left(3^2\right)^9-2^2.3^{20}.\left(2^3\right)^9=5.2^{30}.3^{18}-2^2.3^{20}.2^{27}\)
\(=5.2^{30}.3^{18}-3^{20}.2^{29}=2^{29}.3^{18}.\left(5.2-3^2\right)=2^{29}.3^{18}\)
\(B=5.2^9.\left(2.3\right)^{19}-7.2^{29}.\left(3^3\right)^6=5.2^9.2^{19}.3^{19}-7.2^{29}.3^{18}=5.2^{28}.3^{19}-7.2^{29}.3^{18}\)
\(=2^{28}.3^{18}.\left(5.3-7.2\right)=2^{28}.3^{18}\)
=> \(A:B=\left(2^{29}.3^{18}\right):\left(2^{28}.3^{18}\right)=\frac{\left(2^{29}.3^{18}\right)}{\left(2^{28}.3^{18}\right)}=2\)
b. kiểm tra lại đề bài nhé
a, A= 5x415 x 99 - 4x320x 89 = 5x230x318-22x 227x320
=229x318(2x5-32)=229x318
B=5x29x619-7x229x276=5x29x219x3197x229x318
=238x318(5x3-7x2)=228-318
->A:B= 229x318:228:318=2
1
a) \(\left(20.2^2+12.2^2-48.2^2\right):8^2\)
\(=\left[\left(20+12-48\right).2^2\right]:8^2\)
\(=\left(16.2^2\right):8^2\)
\(=\left(4^2.2^2\right):8^2\)
\(=\left(4.2\right)^2:8^2\)
\(=8^2:8^2\)
= 1